Identification and Functional Verification of MicroRNAs in the Obese Rat With Erectile Dysfunction. Issue 4 (29th September 2017) - Bai, Yunlong; Zhang, Liangshuan; Jiang, Yanan; Ju, Jiaming; Li, Guiyang; Xu, Juan; Jiang, Xing; Zhang, Peng; Lang, Linchuan; Sadkovaya, Olga; Glybochko, Peter V.; Zhang, Wei; et al.
Abstract: Introduction: Obesity is a potential risk factor for erectile dysfunction (ED). MicroRNAs (miRNAs) regulate the expression of genes involved in various pathophysiologic processes. Aim: To identify the miRNA profile in the corpus cavernosum (CC) of obese rats with ED and elucidate the potential function of miRNA in the pathogenesis of ED. Methods: Obesity was induced in rats by a high-fat diet. After the erectile function test, experimental animals were divided into two groups: obese rats with ED and obese rats with normal erectile function. The CCs from these rats were collected for miRNA microarray analysis. The results were verified by real-time polymerase chain reaction analysis. Subsequently, the targets of differentially expressed miRNAs were predicted. Bioinformatics analysis was applied to predict the functions of differentially expressed miRNAs in ED. Apomorphine-induced penile erection and intracavernous pressure measurements were used to evaluate the effects of miRNA on the erectile function of rats. Main Outcome Measures: MiRNA expression in the CC of obese rats with ED and those with normal erectile function was detected by miRNA microarray analysis. Candidate miRNAs were validated by real-time polymerase chain reaction. Bioinformatics analysis was used to predict the functions of miRNAs. Apomorphine-induced penile erection and intracavernous pressure measurements were used to reflect the erectile function of rats. Results: Sixty-eight miRNAs were differentially expressed in the CC of obese rats with ED (≥1.5-fold change). The real-time polymerase chain reaction results were consistent with the miRNA microarray analysis results. Specifically, miR-328a was significantly upregulated in rats with ED compared with control rats and was chosen for functional evaluation in the pathogenesis of ED. Overexpression of miR-328a noticeably decreased the erectile response to apomorphine and the expression of heme oxygenase-1. Conclusion: MiRNAs are involved in the pathogenesis of obesity-related ED. MiR-328a might facilitate the induction of ED.